SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BANTUAN DARI PEMERINTAH UNTUK SISWA TIDAK MAMPU DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) PADA SMP PERMATA DEPOK - Firdani, Muhammad Fiqih; Aryo, Ganang; Lubis, Baginda Oloan (Universitas Methodist Indonesia, 2025)
This study aims to develop a Decision Support System (DSS) for the process of receiving government assistance for underprivileged students at SMP Permata Depok. The system is designed using the Simple Additive Weighting (SAW) method to help the school determine aid recipients more objectively and efficiently. The SAW method was chosen for its ability to provide structured assessments based on predetermined criteria, such as parental income, family dependents, and academic achievements. The research process involves collecting data on eligible students, determining the weight for each criterion, and calculating the final score for each potential aid recipient. The result of this system is a prioritized list of aid recipients that can be used by the school as a recommendation in decision-making. The implementation of this DSS is expected to improve transparency and accuracy in the selection process, minimizing subjectivity and potential errors in assessments. Evaluation of the system shows that the SAW method is effective in supporting fair and targeted decisions for students in need of assistance.